Hierarchical Cobalt Phosphide Hollow Nanocages toward Electrocatalytic Ammonia Synthesis under Ambient Pressure and Room Temperature. Issue 12 (23rd August 2018) - Guo, Wenhan; Liang, Zibin; Zhao, Junliang; Zhu, Bingjun; Cai, Kunting; Zou, Ruqiang; Xu, Qiang
Abstract: Electrochemical nitrogen reduction reaction (NRR) under room temperature and ambient pressure is a promising energy‐ and environmental‐friendly method for ammonia synthesis, which currently highly relies on the energy‐consuming Haber‐Bosch process with enormous CO2 emissions. This study reports the synthesis of a noble‐metal‐free CoP hollow nanocage (CoP HNC) catalyst from a metal‐organic framework precursor through a layered‐double‐hydroxide intermediate, and the use as the cathode for electrochemical NRR. The 3D hierarchical nanoparticle–nanosheet–nanocage structure provides rich surface active sites for nitrogen adsorption and reduction. When applied for NRR, CoP HNC exhibits exciting performance with high Faraday efficiency at low overpotentials (7.36% at 0 V vs reversible hydrogen electrode [RHE]), and the ammonia yield rate increases exponentially at more negative potential, reaching 10.78 µg h −1 at −0.4 V (vs RHE) with good selectivity (no hydrazine produced) under ambient conditions. This noble‐metal‐free electrocatalyst with promising performance demonstrates the unique potential of transition metal and their compounds in the field of NRR, providing new perspectives to rational catalyst design and mechanism study. Abstract : Using cobalt phosphide hollow nanocage as a heterogeneous catalyst, electrochemical nitrogen reduction reaction is enabled with high NH3 yield (10.78 µg h −1 at −0.4 V vs reversible hydrogen electrode [RHE]), high Faraday efficiency (7.36% at 0 V vs RHE), and 100% selectivity for NH3 under room temperature and ambient pressure.